2021
DOI: 10.1002/aenm.202100339
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electrochemical CO2 Reduction using Ce(Mn,Fe)O2 with La(Sr)Cr(Mn)O3 Cathode for High‐Temperature Solid Oxide Electrolysis Cells

Abstract: is mostly dominated by the cathode reaction related to the CO/CO 2 redox couple on the electrode surface. SOECs mostly utilize materials and techniques relevant to solid oxide fuel cells (SOFCs), as they operate in the reverse mode of SOFCs. However, some materials have not been specifically tailored for CO 2 electrolysis conditions. Thus, several research groups have extensively searched for durable fuel electrodes that are suitable for both SOFC and SOEC conditions and provide high catalytic reactivity compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…To further explore the factors affecting the catalytic activity of R-PSCFM, the distribution of relaxation time (DRT) method was used, and the results are shown in Figure S3. Four peaks are obtained, representing P 1 , P 2 , P 3 , and P 4 , respectively, corresponding to the low-frequency region (LF), medium-frequency region (IF), and high-frequency region (HF) . Based on the Adler–Lane–Steele model, the LF region corresponding to the P 1 peak reflects the gas diffusion process, the IF region corresponding to P 2 and P 3 peaks reflects the ion surface exchange process, and the HF region corresponding to the P 4 peak reflects the interface charge transfer process .…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the factors affecting the catalytic activity of R-PSCFM, the distribution of relaxation time (DRT) method was used, and the results are shown in Figure S3. Four peaks are obtained, representing P 1 , P 2 , P 3 , and P 4 , respectively, corresponding to the low-frequency region (LF), medium-frequency region (IF), and high-frequency region (HF) . Based on the Adler–Lane–Steele model, the LF region corresponding to the P 1 peak reflects the gas diffusion process, the IF region corresponding to P 2 and P 3 peaks reflects the ion surface exchange process, and the HF region corresponding to the P 4 peak reflects the interface charge transfer process .…”
Section: Resultsmentioning
confidence: 99%
“…The positions of the characteristic peaks related to IF and LF shift to higher frequencies, suggesting that the electrochemical reaction kinetics should be accelerated. In contrast, after the reduction treatment, the exsolved Ni metal and the increased oxygen vacancies supply more active reaction sites for CO 2 adsorption and activation, while the formed metal-oxide heterostructure with strong interaction enhances the surface exchange reactions (Lee et al, 2021;Zhang L. H. et al, 2022). This occurrence indicates that the CO 2 -RR performance of the Ni@SFNTM Frontiers in Chemistry frontiersin.org cathode is enhanced.…”
Section: Materials Structural Characterizationmentioning
confidence: 99%
“…However, certain inevitable issues hinder its further application, including Ni oxidation during the CO 2 /CO redox reaction process in the absence of a safe gas (H 2 /CO), carbon deposition at high CO concentrations, and Ni particle growth during long-term operation ( Dong et al, 2017 ; Sciazko et al, 2021 ; Yang et al, 2022 ). Materials comprising perovskite oxide with mixed ionic-electronic conductivity, such as Sr 2 Fe 1.5 Mo 0.5 O 6-δ (SFM), show promise for SOEC, and exhibit excellent redox stability, coke resistance, and long-term stability ( Li et al, 2017a ; Zhang et al, 2021 ). Nevertheless, compared with the Ni-YSZ cathode material, SFM oxide exhibits weak chemical CO 2 adsorption and inadequate catalytic activity for CO 2 -RR, which limits the performance of CO 2 electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…For SOECs conditions specifically, DFT calculations showed that both the tetravalent Rh, Ir and Pt 52 and the trivalent Gd 53 are expected to reduce the energy of oxygen vacancy formation at the surface of ceria. Promising results on the beneficial effect of doping ceria for the electrochemical reduction of CO 2 are also reported in a number of experimental studies employing technological electrodes, 54–60 even though a clear correlation between the presence of dopants and the electrochemical performance is hindered by the absence of well-controlled experimental conditions.…”
Section: Introductionmentioning
confidence: 96%